Generation of C-terminal Sequences of Human Renalase-1 and Renalase-2 Encoded by Alternative Exons - Fedchenko, V.I.; Kaloshin, A.A.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2024)
A method for generation of C-terminal amino acid sequences fused to dihydrofolate reductase (DHFR) and specific for RNLS1 and RNLS2 isoforms of renalase is described. It includes synthesis of nucleotide sequences of alternative exons of RNLS1-9ex and RNLS2-10ex, determining the differences in the primary structure of these proteins, their fusion with the coding sequence of DHFR and expression of these genetic constructs in cells of the E. coli Rosetta cells. Chromatographic purification on a column containing Ni Sepharose resulted in highly purified preparations of reombinant ReI-9ex and ReII-10ex proteins with an electrophoretic purity of about 95%.